The environmental supply and the planting density in the Chrysanthemum development - Angie Arredondo-Hoyos; Marco Abril-Ramírez; Darío Castañeda-Sánchez (Revista Ceres, 2024)
ABSTRACT The objective was to evaluate the influence of the annual behavior of some environmental factors and plant densities on Chrysanthemum plant growth. Four Chrysanthemum cultivars were grown at five densities and established a total of 23 experiments in 2018. The plant and climatic variables determined were the dry weight, height, flower buds, growing degree days (GDD) and daily light integrated (DLI) of each crop cycle of each assay, respectively, as well as the relative humidity. The effect of density on plant growth, as determined by crop cycles established throughout the year, was analyzed graphically and through analysis of variance, followed by a Scheffe post hoc test. It used the multivariate analysis to cluster the crop cycles identified by its week of planting and according to the similarity of plant variables and climatic. The growth reached by the crop cycles under the treatments in all cultivars along the year showed an unimodal behavior. The multivariate analysis lets us define two seasons (I, II) exhibiting significant differences in plant growth and climatic variables behavior. Period I had drier conditions and higher radiation than II and DLI was the most limiting factor in plant development, while the GDDs did not influence it.